If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -4)(x + -8) = 5 Reorder the terms: (-4 + x)(x + -8) = 5 Reorder the terms: (-4 + x)(-8 + x) = 5 Multiply (-4 + x) * (-8 + x) (-4(-8 + x) + x(-8 + x)) = 5 ((-8 * -4 + x * -4) + x(-8 + x)) = 5 ((32 + -4x) + x(-8 + x)) = 5 (32 + -4x + (-8 * x + x * x)) = 5 (32 + -4x + (-8x + x2)) = 5 Combine like terms: -4x + -8x = -12x (32 + -12x + x2) = 5 Solving 32 + -12x + x2 = 5 Solving for variable 'x'. Reorder the terms: 32 + -5 + -12x + x2 = 5 + -5 Combine like terms: 32 + -5 = 27 27 + -12x + x2 = 5 + -5 Combine like terms: 5 + -5 = 0 27 + -12x + x2 = 0 Factor a trinomial. (3 + -1x)(9 + -1x) = 0Subproblem 1
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Subproblem 2
Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9Solution
x = {3, 9}
| 10x^2-3x=6x-8x^2 | | 2x-9=-6 | | 2+5(10)= | | (6x^2y-4xy^2)-(-9x^2y-7xy^2)= | | 2x^2-20x-5525=0 | | 100[0.06(n+10)]= | | 2b^3-4=r^8 | | 50x-4=45x+1 | | 2y^6+9=g^1 | | 50x-1=45x+1 | | -1x-6y=5 | | C-16=18 | | B+127=52 | | -x+6y=5 | | K+6K-13=57 | | 3x*3x-2x+7=0 | | 6-3-(-10)-7+(-13)+33= | | 58(w)(w+8)=x | | (3x-5)(x-2)=0 | | 8-5x-x=14 | | (8x-5x)+(-2-8)= | | X+(3-2x)= | | -3/4+4/-7= | | 3/4+4/7= | | -3/4+-4/7= | | 3x+4y=a | | 10x^3-7x^2-12x=0 | | 3x+12=9x+36 | | 3x+12=9x+39 | | 2(3x+4)-1=9 | | 2x+13=7x+5 | | (x+5)*(x+5)=6 |